Numerical and Experimental Analysis of Base Cavity and Windshield Angle for Aerodynamic Drag Reduction of a Bus - Daniel Hailu Aseba; Ramesh Babu Nallamothu; Abraha Kahsay (Journal of Engineering)
In reaction to increasing gasoline costs, scarcity of fuel, and environmental issues, the automotive sector has concentrated on decreasing aerodynamic drag in order to lower vehicle fuel usage and carbon dioxide emissions. Buses are a popular mode of transportation, and knowing their aerodynamics helps to make them more effective and reduce drag. The purpose of this study was to reduce the Bishoftu bus’s aerodynamic drag by using base cavity configurations and altering the angle of the windshield. ANSYS 19.2 was used to perform a computational fluid dynamics (CFD) simulation to assess the aerodynamic performance of vehicle models at different speeds with 3D CAD models created in SOLIDWORKS 21. Wind tunnel tests were also performed to validate the numerical results of the reference bus model. The drag coefficient results revealed an average error percentage of 6.09% between the CFD and wind tunnel tests. Applying a 12° base cavity angle with a tapered depth of 0.3H to the baseline model reduced the average drag coefficient by 7.06%. The study also looked at how changes in windshield angle affected the baseline model’s aerodynamic properties. It discovered that these changes led to a smaller stagnation pressure region and a maximum average drag coefficient reduction of 17.12%. Additionally, a study was conducted on the combined impact of base cavity layouts and differences in windshield angles. Model 26, which has a 17° windshield angle, a 12° base cavity angle, and a 0.3H tapered base cavity length, obtained the minimal average drag coefficient (Cd) and drag force (Fd) values of 0.4779 and 1420.97 N, respectively. With this improved model, the drag coefficient was lowered by 25.22% and the drag force by 26.6%. This led to a maximum reduction in fuel consumption of 3.66 L/h and the highest average annual CO2 savings of 48.35 tonnes/year. Lastly, by prioritizing the main purpose of the study, the response surface methodology was used to do multiobjective optimization. The best measurements were found to be an 11.54° base cavity angle, a 17° windshield angle, and a tapered base cavity length that was 0.3 times the vehicle’s height (0.3H).